Volcanic activity around Taipei, Taiwan: new data and perspectives on the Tatun Volcano Group - Su-Chin Chang; Mei-Fei Chu; Jui-Pin Wang; Yu-Ming Lai; Sheng-Rong Song; Sidney R. Hemming; Samuel Wai-Pan Ng; Timothy Dylan Chow (Geoscience Letters, 2024)
Abstract The Tatun Volcano Group (TVG) is located at the northern end of Taiwan, ~ 15 km from the center of Taipei, a metropolitan area of over seven million inhabitants. A volcanic eruption by the TVG of any type or scale could cause catastrophic human and economic impacts. This paper summarizes previous geochemical, geophysical, and geochronological reports and highlights why the widely accepted age model does not comport with the latest observations. This study also reports novel 40Ar/39Ar ages for two andesite samples and one basalt sample from the TVG. A sample collected from Chihsingshan yields a robust 40Ar/39Ar age of 0.081 ± 0.005 Ma. This provides the first direct evidence of TVG volcanic activity after 0.1 Ma. Two samples yield 0.28 ± 0.02 Ma for Tatunshan and 0.159 ± 0.017 Ma for Honglushan. The younger ages refute previously proposed age models for the TVG. Along with new drone photos and LiDAR images, the age data help resolve eruptive history and advance understanding of volcanic hazards and hazard mitigation in Taiwan and surrounding areas.